Environmentally friendly material for soil testing and preparation method thereof

By using carboxylated nanocellulose fiber gel material as the carrier of curcumin, the cost and complex problems of lead ion detection equipment in soil in the prior art are solved, and rapid on-site detection with high specificity and sensitivity is achieved, with the advantages of no contact pollution.

CN119281307BActive Publication Date: 2025-03-21SHANDONG XINGFEI CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411823744.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-21
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The prior art has limitations in the detection of lead ion in soil, such as expensive equipment, complex steps and the need for professional and technical personnel, making it difficult to achieve rapid on-site inspection.

Method used

Carboxylated nanocellulose fibers are used as the carrier of curcumin, and a stable carboxylated nanocellulose fiber gel material is formed through ultrasonic dispersion and polyethylene glycol dispersion additives, and environmentally friendly materials for soil detection are prepared through acid vapor gelation and freeze-drying processes.

Benefits of technology

The material exhibits high specificity, sensitivity and accuracy in soil detection, can achieve rapid on-site detection, and has the advantages of no contact pollution, with a visual detection limit of 10 mg/L.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer materials, and specifically relates to an environmentally friendly material for soil detection and a preparation method thereof. The material preparation method comprises the following steps: (1) preparing a carboxylated nanocellulose fiber dispersion; (2) preparing a mixed solution of polyethylene glycol and curcumin; (3) dropping the mixed solution into the carboxylated nanocellulose fiber dispersion; (4) placing the mixture in a light-proof acidic vapor environment for gelation, and freeze-drying to obtain an environmentally friendly material for soil detection. The gel can specifically detect and adsorb lead ions, and has the advantages of high sensitivity and no contact pollution. It is particularly suitable for the specific detection of lead ions in soil containing multiple metal ions. In addition, the material is in solid form, which is convenient for storage and transportation, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an environmentally friendly material for soil detection and a preparation method thereof. Background Art

[0002] As a heavy metal, lead is used in a variety of industries that are closely related to daily life, including but not limited to fuel processing, battery manufacturing, smelting and other fields. This widespread application has led to the widespread distribution of lead and its compounds in the environment, and it is recognized as one of the most harmful elements. The widespread presence of lead will cause soil pollution, which will further affect crops, animals and plants. Through the food chain, lead will eventually be ingested and accumulated by the human body, thus directly threatening human health and safety.

[0003] Traditional analytical methods for detecting lead include large-scale instrumental methods such as atomic absorption spectroscopy, inductively coupled plasma emission mass spectrometry, atomic fluorescence spectroscopy, and high performance liquid chromatography. Usually, the appropriate analytical method is selected according to the sample, lead concentration, and detection limit. Among them, atomic absorption spectroscopy has the advantages of high accuracy, good selectivity, low sample consumption, and a wide range of applications. Inductively coupled plasma mass spectrometry is the first choice for trace detection. It identifies and measures based on the charge-to-mass ratio of metals, and has the advantages of low detection limit, wide detection range, and easy multi-target analysis. In addition, the atomic fluorescence method has a fast analysis speed and its cost is lower than that of inductively coupled plasma emission mass spectrometry, but the carrier gas used has certain requirements for the acidity of the system. Although the above methods have their own advantages, they have limitations such as expensive testing equipment, complicated steps, and the need for professional technicians, and are not suitable for on-site detection.

[0004] In order to effectively detect and control lead ions in soil, many new analytical methods that are fast, accurate, and simple have been developed. For example, analytical methods using nanomaterials as signal probes, including precious metal nanoparticles, quantum dots, nanofibers, and other nanomaterials, can detect lead ions by using the combination of materials and metal ions to cause changes in the characteristics of the signal probe. In this type of method, the mechanical stability and sensitivity of the material are the key factors affecting the sensing performance. Summary of the invention

[0005] The purpose of the present invention is to provide an environmentally friendly material for soil detection and a preparation method thereof, which not only simplifies the preparation process, but also shows certain advantages in the specificity, sensitivity and accuracy in the field of soil detection, has the ability to be applied to rapid on-site detection, and provides a new solution to solve practical problems in soil heavy metal detection.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0008] (1) ultrasonically dispersing the carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion;

[0009] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is (1000-2000): (1-10): 1;

[0010] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution;

[0011] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 35-50°C.

[0012] Curcumin is a hydrophobic and lipophilic natural polyphenol extracted from turmeric, which has pH-sensitive, antibacterial, antioxidant and anti-inflammatory effects. Due to its β-diketone part, curcumin exists in keto-enol tautomerism. Curcumin has been shown to bind to many signal molecules. By monitoring the color change of curcumin, a colorimetric sensor can be established to achieve accurate detection of different target substances. Specifically, curcumin itself is yellow. Due to its polyphenol structure and keto-enol interchange structure, it can complex with lead ions to form a stable complex, thereby causing it to change from yellow to red, which is an ideal choice for the removal and sensing of heavy metals such as lead ions.

[0013] However, curcumin has poor dispersion stability, and how to prepare it into a detection material is a difficult problem that needs to be overcome. Cellulose is a high molecular polymer with the most abundant natural resources. As a natural high molecular material, it is more easily decomposed by microorganisms than synthetic high molecular weight polymers. It has no toxicity and will not pollute the environment, and has good biodegradability and biocompatibility. Therefore, the present invention uses carboxylated nano cellulose fibers as a carrier of curcumin. Carboxylated nano cellulose fiber gel is a hydrophilic polymer material with a three-dimensional structure, with a porous structure and abundant chemical functional groups inside. It can swell into several times of its own volume in water, showing extremely strong water absorption and water retention characteristics. It is precisely because of the water absorption and water retention characteristics of carboxylated nano cellulose fiber gel, and the presence of hydrophilic active groups on the surface of carboxylated nano cellulose fiber gel matrix, hydrogen bonds or electrostatic adsorption can occur with heavy metal ions, thereby adsorbing and capturing heavy metal ions, which is conducive to the color development reaction of curcumin. Furthermore, due to the presence of carboxyl groups on the surface of carboxylated nanocellulose fibers, during the heating gelation process, they can react with the phenolic hydroxyl groups on curcumin, thereby improving the adhesion and adhesion efficiency of curcumin and the stability of the detection material; at the same time, curcumin acts as a cross-linking agent, promoting the formation of the gel structure. Under the action of acidic vapor, the reaction can be carried out without a catalyst, thereby improving the purity and sensitivity of the detection material and avoiding the decrease in detection sensitivity caused by the introduction of a catalyst. At the same time, the aerogel prepared by the freeze-drying process improves the mechanical properties of the material and is convenient to use.

[0014] In order to improve the dispersibility of curcumin in carboxylated nanocellulose fiber gel and enhance its detection effect. The present invention adds polyethylene glycol as a dispersing aid. Polyethylene glycol is a non-ionic surfactant that can form colloidal particles in a solution and effectively prevent the aggregation of particles through a steric hindrance effect. Moreover, the polyethylene glycol molecule has a serpentine structure in the solution, which makes it easy for polyethylene glycol to establish a strong hydrogen bond on the surface of curcumin, and its oxygen ether group easily produces a homonymous ion affinity with the surface of oxygen-containing colloid particles. This characteristic enables polyethylene glycol to be easily adsorbed on the surface of the colloid particles to form a layer of polymer protective film that surrounds the colloid particles. When colloidal particles with the same charge approach each other, the electrostatic repulsion plus the steric hindrance effect of the polymer play a dispersing role.

[0015] Furthermore, the solvent in step (1) is a mixed solvent of ethanol and deionized water.

[0016] Furthermore, in step (1), the ultrasonic power is 100-200 W, and the ultrasonic temperature is 30-50° C.

[0017] Furthermore, in step (1), the concentration of the carboxylated nanocellulose fiber dispersion is 1-3 wt %; and the carboxyl content of the carboxylated nanocellulose fibers is 1.2-3 mmol / g.

[0018] Furthermore, in step (2), the concentration of curcumin in the curcumin mixed solution is 0.02-0.06 wt %.

[0019] Furthermore, in step (2), the number average molecular weight of the polyethylene glycol is 200-800. Furthermore, the number average molecular weight of the polyethylene glycol is 400-600.

[0020] Furthermore, in step (2), the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is (1000-2000): (3-6): 1. When the molecular weight is low, the polyethylene glycol molecular chain is short and the dispersion effect is limited; when the molecular weight is high, the solubility and dispersibility are reduced, which is not conducive to the dispersion of curcumin. When the amount of carboxylated nanocellulose fibers is too low, the gel network is sparse, which is not conducive to the adsorption of curcumin; when the amount of carboxylated nanocellulose fibers is too high, the gel porosity is reduced, which is not only not conducive to the infiltration of curcumin into the gel, but also not conducive to the adsorption of heavy metal ions, affecting the mechanical properties of the gel and the detection effect.

[0021] Furthermore, in step (3), the stirring rate is 300-600 rpm.

[0022] Furthermore, in step (4), the acid vapor is at least one of hydrochloric acid vapor, formic acid vapor, and acetic acid vapor; and the gelation time is 6-10 hours. Furthermore, the heating temperature of the gelation process is 40-50°C. The appropriate heating temperature can promote the reaction between the phenolic hydroxyl group on the curcumin and the carboxyl group on the carboxylated nanocellulose fibers. If the reaction temperature is too high, it is not only not conducive to the formation of the gel pore structure, but also may destroy the gelation process.

[0023] On the other hand, the present invention also provides an environmentally friendly material for soil detection. Based on the heavy metal complex color change responsiveness of curcumin, a colorimetric carboxylated nanocellulose fiber gel material with stable curcumin loading is constructed. The gel can specifically detect and adsorb lead ions, and has the advantages of high sensitivity and no contact pollution. 2+ Selective, encounter Pb 2+ When the gel material changes from yellow to red, 2+ , Cu 2+ 、Zn 2+ 、Al 3+ Plasma does not produce obvious color reaction; it is particularly suitable for the specific detection of lead ions in soil containing multiple metal ions.

[0024] More importantly, the present invention significantly reduces Pb2+ The detection limit is 10 mg / L by visual inspection. 2+ However, its detection usually requires digital processing with the help of image processing software, and the visual detection limit is too high; and even after digital processing, its detection limit can usually only reach a few milligrams of lead concentration per liter, which does not have the ability to conduct rapid on-site detection.

[0025] Beneficial effects: The present invention prepares a carboxylated nanocellulose fiber gel material that stably loads curcumin. By monitoring the color change of curcumin, a colorimetric sensor can be established to achieve accurate detection of different target substances. The use of carboxylated nanocellulose to prepare a cellulose-based gel as a carrier of curcumin can react with heavy metal ions through hydrogen bonding or electrostatic adsorption, thereby adsorbing and capturing heavy metal ions, which is beneficial to the color development reaction of curcumin. Moreover, the presence of carboxyl groups on the surface of the carboxylated nanocellulose fibers can react with the phenolic hydroxyl groups on the curcumin during the heating gelation process, thereby improving the adhesion and adhesion efficiency of curcumin and improving the stability of the detection material. Polyethylene glycol improves the dispersion loading effect of curcumin. The gel can specifically detect and adsorb lead ions, and has the advantages of high sensitivity and no contact pollution. And the gel material has high sensitivity to Pb 2+ Selective, encounter Pb 2+ When the gel material turns red, the 2+ , Cu 2+ 、Zn 2+ 、Al 3+ Plasma does not produce obvious color reaction; it is particularly suitable for the specific detection of lead ions in soil containing multiple metal ions. In addition, the material is in solid form, which is convenient for storage and transportation, and has broad application prospects. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0029] (1) Ultrasonic dispersion of carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; the solvent is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1; the ultrasonic power is 100 W, the ultrasonic temperature is 50 ° C; the concentration of the carboxylated nanocellulose fiber dispersion is 1 wt%; the carboxyl content of the carboxylated nanocellulose fibers is 2 mmol / g;

[0030] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is 1000:3:1; the concentration of curcumin in the curcumin mixed solution is 0.02wt%; and the number average molecular weight of polyethylene glycol is 400;

[0031] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; the stirring rate is 300 rpm;

[0032] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 40° C.; the acidic vapor is hydrochloric acid vapor; and the gelation time is 10 hours.

[0033] Example 2

[0034] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0035] (1) Ultrasonic dispersion of carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; the solvent is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1; the ultrasonic power is 200 W, the ultrasonic temperature is 30 ° C; the concentration of the carboxylated nanocellulose fiber dispersion is 3wt%; the carboxyl content of the carboxylated nanocellulose fibers is 2mmol / g;

[0036] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is 2000:6:1; the concentration of curcumin in the curcumin mixed solution is 0.02wt%; and the number average molecular weight of polyethylene glycol is 600;

[0037] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; the stirring rate is 600 rpm;

[0038] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 50° C.; the acidic vapor is hydrochloric acid vapor; and the gelation time is 6 hours.

[0039] Example 3

[0040] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0041] (1) Ultrasonic dispersion of carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; the solvent is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1; the ultrasonic power is 100 W, the ultrasonic temperature is 35 ° C; the concentration of the carboxylated nanocellulose fiber dispersion is 1.2 wt%; the carboxyl content of the carboxylated nanocellulose fibers is 2 mmol / g;

[0042] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is 1000:6:1; the concentration of curcumin in the curcumin mixed solution is 0.02wt%; and the number average molecular weight of polyethylene glycol is 400;

[0043] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; the stirring rate is 600 rpm;

[0044] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 45°C; the acidic vapor is hydrochloric acid vapor; and the gelation time is 9 hours.

[0045] Example 4

[0046] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0047] (1) Ultrasonic dispersion of carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; the solvent is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1; the ultrasonic power is 120 W, the ultrasonic temperature is 45 ° C; the concentration of the carboxylated nanocellulose fiber dispersion is 1.5 wt%; the carboxyl content of the carboxylated nanocellulose fibers is 2 mmol / g;

[0048] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is 1300:3.5:1; the concentration of curcumin in the curcumin mixed solution is 0.02wt%; and the number average molecular weight of polyethylene glycol is 400;

[0049] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; the stirring rate is 400 rpm;

[0050] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 42°C; the acidic vapor is hydrochloric acid vapor; and the gelation time is 8.5 hours.

[0051] Example 5

[0052] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0053] (1) Ultrasonic dispersion of carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; the solvent is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1; the ultrasonic power is 180 W, the ultrasonic temperature is 45 ° C; the concentration of the carboxylated nanocellulose fiber dispersion is 2.5 wt%; the carboxyl content of the carboxylated nanocellulose fibers is 2 mmol / g;

[0054] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is 1700:5.5:1; the concentration of curcumin in the curcumin mixed solution is 0.02wt%; and the number average molecular weight of polyethylene glycol is 600;

[0055] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; the stirring rate is 550 rpm;

[0056] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 48°C; the acidic vapor is hydrochloric acid vapor; and the gelation time is 7 hours.

[0057] Example 6

[0058] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0059] (1) Ultrasonic dispersion of carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; the solvent is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1; the ultrasonic power is 150 W, the ultrasonic temperature is 40 ° C; the concentration of the carboxylated nanocellulose fiber dispersion is 2 wt%; the carboxyl content of the carboxylated nanocellulose fibers is 2 mmol / g;

[0060] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is 1500:5:1; the concentration of curcumin in the curcumin mixed solution is 0.02wt%; and the number average molecular weight of polyethylene glycol is 400;

[0061] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; the stirring rate is 400 rpm;

[0062] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 45°C; the acidic vapor is hydrochloric acid vapor; and the gelation time is 7 hours.

[0063] Example 7

[0064] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0065] (1) Ultrasonic dispersion of carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; the solvent is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1; the ultrasonic power is 150 W, the ultrasonic temperature is 40 ° C; the concentration of the carboxylated nanocellulose fiber dispersion is 2 wt%; the carboxyl content of the carboxylated nanocellulose fibers is 2 mmol / g;

[0066] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is 1500:1:1; the concentration of curcumin in the curcumin mixed solution is 0.02wt%; and the number average molecular weight of polyethylene glycol is 400;

[0067] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; the stirring rate is 400 rpm;

[0068] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 45°C; the acidic vapor is hydrochloric acid vapor; and the gelation time is 7 hours.

[0069] Example 8

[0070] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0071] (1) Ultrasonic dispersion of carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; the solvent is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1; the ultrasonic power is 150 W, the ultrasonic temperature is 40 ° C; the concentration of the carboxylated nanocellulose fiber dispersion is 2 wt%; the carboxyl content of the carboxylated nanocellulose fibers is 2 mmol / g;

[0072] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is 1500:10:1; the concentration of curcumin in the curcumin mixed solution is 0.02wt%; and the number average molecular weight of polyethylene glycol is 400;

[0073] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; the stirring rate is 400 rpm;

[0074] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 45°C; the acidic vapor is hydrochloric acid vapor; and the gelation time is 7 hours.

[0075] Example 9

[0076] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0077] (1) Ultrasonic dispersion of carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; the solvent is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1; the ultrasonic power is 150 W, the ultrasonic temperature is 40 ° C; the concentration of the carboxylated nanocellulose fiber dispersion is 2 wt%; the carboxyl content of the carboxylated nanocellulose fibers is 2 mmol / g;

[0078] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is 1500:5:1; the concentration of curcumin in the curcumin mixed solution is 0.02wt%; and the number average molecular weight of polyethylene glycol is 200;

[0079] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; the stirring rate is 400 rpm;

[0080] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 45°C; the acidic vapor is hydrochloric acid vapor; and the gelation time is 7 hours.

[0081] Example 10

[0082] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0083] (1) Ultrasonic dispersion of carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; the solvent is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1; the ultrasonic power is 150 W, the ultrasonic temperature is 40 ° C; the concentration of the carboxylated nanocellulose fiber dispersion is 2 wt%; the carboxyl content of the carboxylated nanocellulose fibers is 2 mmol / g;

[0084] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is 1500:5:1; the concentration of curcumin in the curcumin mixed solution is 0.02wt%; and the number average molecular weight of polyethylene glycol is 800;

[0085] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; the stirring rate is 400 rpm;

[0086] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 45°C; the acidic vapor is hydrochloric acid vapor; and the gelation time is 7 hours.

[0087] Embodiment 11

[0088] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0089] (1) Ultrasonic dispersion of carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; the solvent is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1; the ultrasonic power is 150 W, the ultrasonic temperature is 40 ° C; the concentration of the carboxylated nanocellulose fiber dispersion is 2 wt%; the carboxyl content of the carboxylated nanocellulose fibers is 2 mmol / g;

[0090] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is 1500:5:1; the concentration of curcumin in the curcumin mixed solution is 0.02wt%; and the number average molecular weight of polyethylene glycol is 400;

[0091] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; the stirring rate is 400 rpm;

[0092] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 35°C; the acidic vapor is hydrochloric acid vapor; and the gelation time is 7 hours.

[0093] Comparative Example 1

[0094] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0095] (1) Ultrasonic dispersion of carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; the solvent is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1; the ultrasonic power is 150 W, the ultrasonic temperature is 40 ° C; the concentration of the carboxylated nanocellulose fiber dispersion is 2 wt%; the carboxyl content of the carboxylated nanocellulose fibers is 2 mmol / g;

[0096] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is 500:5:1; the concentration of curcumin in the curcumin mixed solution is 0.02wt%; and the number average molecular weight of polyethylene glycol is 400;

[0097] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; the stirring rate is 400 rpm;

[0098] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 45°C; the acidic vapor is hydrochloric acid vapor; and the gelation time is 7 hours.

[0099] Comparative Example 2

[0100] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0101] (1) Ultrasonic dispersion of carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; the solvent is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1; the ultrasonic power is 150 W, the ultrasonic temperature is 40 ° C; the concentration of the carboxylated nanocellulose fiber dispersion is 2 wt%; the carboxyl content of the carboxylated nanocellulose fibers is 2 mmol / g;

[0102] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is 3000:5:1; the concentration of curcumin in the curcumin mixed solution is 0.02wt%; and the number average molecular weight of polyethylene glycol is 400;

[0103] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; the stirring rate is 400 rpm;

[0104] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 45°C; the acidic vapor is hydrochloric acid vapor; and the gelation time is 7 hours.

[0105] Comparative Example 3

[0106] A method for preparing an environmentally friendly material for soil testing comprises the following steps:

[0107] (1) Ultrasonic dispersion of carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; the solvent is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1; the ultrasonic power is 150 W, the ultrasonic temperature is 40 ° C; the concentration of the carboxylated nanocellulose fiber dispersion is 2 wt%; the carboxyl content of the carboxylated nanocellulose fibers is 2 mmol / g;

[0108] (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is 1500:5:1; the concentration of curcumin in the curcumin mixed solution is 0.02wt%; and the number average molecular weight of polyethylene glycol is 400;

[0109] (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; the stirring rate is 400 rpm;

[0110] (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 65°C; the acidic vapor is hydrochloric acid vapor; and the gelation time is 7 hours.

[0111] Performance Test:

[0112] The environmentally friendly materials for soil testing prepared in the examples and comparative examples were placed on a universal testing machine for compression testing to test their compression strength.

[0113] The environmentally friendly materials for soil testing prepared in the examples and comparative examples were placed in a solution with a pH of 6 and a concentration of 0, 1 mg / L, 5 mg / L, 10 mg / L, 15 mg / L, 20 mg / L, 30 mg / L, 50 mg / L, 100 mg / L, 300 mg / L, and 500 mg / L of Pb 2+ The lowest Pb content in the solution was measured by visually observing the color change of the environmentally friendly material in the soil after standing for 10 minutes in the dark. 2+ Concentration, as Pb 2+ Detection limit.

[0114] The environmentally friendly soil testing materials prepared in the examples and comparative examples were placed in a solution containing Ni 2+ , Cu 2+ 、Zn 2+ 、Al 3+ The solution of one of the ions was placed in a light-proof condition for 10 minutes and then taken out to visually inspect whether the color of the environmentally friendly material tested in the soil has changed.

[0115]

[0116]

[0117] As can be seen from Table 1, the present invention prepares a carboxylated nanocellulose fiber gel material with a stable curcumin loading. The gel can specifically detect and adsorb lead ions, has a low lead ion detection limit, has the advantages of high sensitivity and no contact pollution, has a low visual detection limit, and has the ability of rapid on-site detection. And the gel material has a high sensitivity for Pb 2+ Selective, encounter Pb 2+ When the gel material turns red, the 2+ , Cu 2+ 、Zn 2+ 、Al 3+ Plasma does not undergo obvious color development reaction; it is particularly suitable for the specific detection of lead ions in soil containing a variety of metal ions. Specifically, it can be seen from Comparative Examples 1-2 that the amount of carboxylated nanocellulose fibers used as the gel matrix material should be controlled. When the amount of carboxylated nanocellulose fibers is too low, the gel network is sparse, which is not conducive to the adsorption of curcumin; when the amount of carboxylated nanocellulose fibers is too much, the gel porosity is reduced, which is not only not conducive to the immersion of curcumin into the gel, but also not conducive to the adsorption of heavy metal ions, affecting the detection effect. At the same time, Comparative Example 3 shows that the temperature during the gelation heating process cannot be too high. Appropriate heating temperature can promote the reaction of phenolic hydroxyl groups on curcumin with carboxyl groups on carboxylated nanocellulose fibers. However, the reaction temperature is not only not conducive to the formation of the gel pore structure, but also may destroy the gelation process, resulting in poor mechanical properties of the detection material.

[0118] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing an environmentally friendly material for soil testing, characterized in that: The following steps are involved: (1) ultrasonically dispersing the carboxylated nanocellulose fibers in a solvent to obtain a carboxylated nanocellulose fiber dispersion; (2) dissolving and dispersing polyethylene glycol and curcumin in ethanol to obtain a curcumin mixed solution; the mass ratio of carboxylated nanocellulose fibers to polyethylene glycol and curcumin is (1000-2000):(3-6):1; the number average molecular weight of polyethylene glycol is 200-800; (3) adding the curcumin mixed solution dropwise into the carboxylated nanocellulose fiber dispersion while stirring to obtain a mixed solution; (4) The mixed solution is heated and placed in a light-proof acidic vapor environment for gelation to prepare a hydrogel; the hydrogel is freeze-dried to obtain an environmentally friendly material for soil testing; the heating temperature is 35-50°C.

2. The method for preparing the environmentally friendly material for soil testing according to claim 1, characterized in that: The solvent in step (1) is a mixed solvent of ethanol and deionized water.

3. The method for preparing the environmentally friendly material for soil testing according to claim 1, characterized in that: In step (1), the ultrasonic power is 100-200 W and the ultrasonic temperature is 30-50° C.

4. The method for preparing the environmentally friendly material for soil testing according to claim 1, characterized in that: In step (1), the concentration of the carboxylated nanocellulose fiber dispersion is 1-3wt%; and the carboxyl content of the carboxylated nanocellulose fibers is 1.2-3mmol / g.

5. The method for preparing the environmentally friendly material for soil testing according to claim 1, characterized in that: The curcumin concentration in the curcumin mixed solution in step (2) is 0.02-0.06wt%.

6. The method for preparing the environmentally friendly material for soil testing according to claim 1, characterized in that: The stirring rate in step (3) is 300-600 rpm.

7. The method for preparing the environmentally friendly material for soil testing according to claim 1, characterized in that: In step (4), the acid vapor is at least one of hydrochloric acid vapor, formic acid vapor and acetic acid vapor; and the gelation time is 6-10 hours.

8. An environmentally friendly material for soil testing, characterized by: The environmentally friendly material for soil testing is prepared by the preparation method of any one of claims 1 to 7.

Citation Information

Patent Citations

  • Electrostatic spinning nanofiber support for rapid field detection and lead ion removal

    CN107151863A

  • Oxidized cellulose / polyvinyl alcohol / curcumin composite hydrogel with antibacterial property and preparation method thereof

    CN117487197A